Active surveillance of choroidal neovascularisation in children: incidence, aetiology and management findings from a national study in the UK. Issue 4 (26th August 2017) - Moosajee, Mariya; Abbouda, Alessandro; Foot, Barnaby; Bunce, Catey; Moore, Anthony T; Acheson, James
Abstract : Background/Aims: To determine the UK incidence, demographics, aetiology, management and visual outcome for children developing choroidal neovascularisation (CNV). Methods: A prospective population-based observational study of routine practice via the British Ophthalmological Surveillance Unit between January 2012 and December 2013 with subsequent 1-year follow-up in children under 16 years old with newly diagnosed CNV. Results: Twenty-seven children with CNV were reported. The UK estimated annual incidence for those aged 16 and under was 0.21 per 100 000 (95% CI 0.133 to 0.299). The mean age was 11.1 years (SD 3.9, range 4–16). Fourteen were female. Seventy-seven per cent (22 patients) were Caucasian British. Twenty-three children (85%) had unilateral disease. The most common aetiology included inflammatory retinochoroidopathy (n=9), optic disc abnormalities (n=9) and idiopathic (n=5). Optical coherence tomography was performed in all cases and fundus fluorescein angiography in 61%. Management included observation only (n=10), anti-vascular endothelial growth factor (anti-VEGF) injection of bevacizumab (n=14) or ranibizumab (n=2), or both (n=1), and additional use of oral (n=1) and local (periocular n=2 and intravitreal n=2) steroids in five children with inflammatory retinochoroidopathy. The mean number of anti-VEGF injections was 2±1, with eight patients receiving only one injection. The mean (SD) best corrected visual acuity in LogMAR was 0.91 (0.53) at presentation and 0.74 (0.53) at 1-year follow-up (p=0.09). Conclusion: This is the first population-based prospective study of CNV in children. This is a rare disorder with a poor visual prognosis irrespective of CNV location and the use of anti-VEGF therapy.